STRATEGI MEDIA KOMUNIKASI VISUAL EDUKASI TENTANG CRYPTOCURRENCY UNTUK INVESTOR PEMULA - Amos Natanael; Andrew Tjahja Susanto; Dennis Nathanael; Desnalia Maharani; Owen Leonardo; Anny Valentina (Jurnal Muara Ilmu Sosial, Humaniora, dan Seni, 2022)
Cryptocurrency is a digital currency that is used as an alternative and is traded using the cryptography method. Recently the covid-19 pandemic has struck the whole world and became a huge factor for the working environment, especially for on-site jobs. The situation has caused a lot of people to lose income for their jobs. One method to earn passive income is to use cryptocurrency. The only problem is that the general public doesn’t have the proper information about this digital currency, even though people are willing to give it a try. Using qualitative observation, the data can be obtained from online surveys and interviews. Based on the results, media is something that is inseparable in daily life. The profit percentage of cryptocurrency is quite large, but if the value drops then the user will experience loss. Using crypto apps usually needs a good internet connection for monitoring the prices, it also attracts a lot of online scams.  There is a rational and an irrational way to deal with online investment. The rational way is for people to realize the risks and rewards of using cryptocurrency. The irrational way is for people to use cryptocurrency for their main source of income. The irrational method is very ineffective and usually leads to mental diseases caused by the problems of cryptocurrency itself. In conclusion, the method to spread awareness about cryptocurrency is to create booths, YouTube video, ads, especially website ads so that a lot of people can access the information easily.